Analgesic and Anti-Arthritic Potential of Methanolic Extract and Palmatine Obtained from Annona squamosa Leaves - Caren Naomi Aguero Ito; Elisangela dos Santos Procopio; Natália de Matos Balsalobre; Lucas Luiz Machado; Saulo Euclides Silva-Filho; Taíse Fonseca Pedroso; Caroline Caramano de Lourenço; Rodrigo Juliano Oliveira; Arielle Cristina Arena; Marcos José Salvador; Cândida Aparecida Leite Kassuya (MDPI AG, 2024)
Background/Objectives: Annona squamosa is used in folk medicine to treat pain and arthritis. Palmatine is an alkaloid isolated from several plants, including A. squamosa leaves. The aim of the present study was to investigate the analgesic, anti-arthritic, and anti-inflammatory potential of the methanolic extract of A. squamosa (EMAS) and palmatine. Methods: The chemical profile of EMAS was evaluated by ultra high-performance liquid chromatography with electrospray ionization coupled to mass spectrometry (UHPLC-ESI/MS). EMAS and palmatine were evaluated in carrageenan-induced pleurisy, zymosan-induced joint inflammation, formalin-induced nociception, and tumor necrosis factor (TNF)-induced mechanical hyperalgesia in experimental models in mice. A cytotoxicity test of EMAS and palmatine was performed using a methylthiazolidiphenyl-tetrazolium (MTT) bromide assay. Results: The analysis of the chemical profile of the extract showed the presence of palmatine, liriodenine, and anonaine. Oral administration of EMAS and palmatine significantly reduced leukocyte migration and oxide nitric production in the carrageenan-induced pleurisy model. EMAS and palmatine reduced mechanical hyperalgesia, leukocyte migration, and edema formation in the joint inflammation induced by zymosan. In the formalin test, palmatine was effective against the second-phase nociceptive response, mechanical hyperalgesia, and cold allodynia. In addition, palmatine reduced mechanical hyperalgesia induced by TNF. EMAS and palmatine did not demonstrate cytotoxicity. Conclusions: The present study showed that A. squamosa and palmatine are analgesic and anti-inflammatory agents, and that the anti-hyperalgesic properties of palmatine may involve the TNF pathway. Palmatine may be one of the compounds responsible for the anti-hyperalgesic and/or anti-arthritic properties of this medicinal plant.